(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
The comfort of wearing suits, a staple of formal attire, is crucial for the human body. Studies and surveys indicate that individuals often experience discomfort and shoulder pain due to ill-fitting suits, leading to uneven pressure distribution and subsequent fatigue. Due to the increasing demands of consumers for clothing, the issue of discomfort in the shoulder area of women’s suits requires improvement. However, most research on women’s suits has focused on aesthetic aspects, with little attention given to the pressure comfort of the shoulder region. This study bridges this gap by examining pattern optimisation and pressure comfort in women’s suits. The study uses Martin’s measuring instruments and 3D scanning to gather shoulder data from young women. The goal is to understand the typical shape and structure of human shoulders. With this information, we develop a method to optimise shoulder patterns in clothing, ensuring they can be adapted to fit different shoulder types comfortably. The research identifies the relationship between the shoulder slope angles of suit patterns and human shoulder shapes, formulating an equation to link body morphology with pattern design. This study can facilitate designers’ understanding of the relationship between human shoulder morphology and clothing patterns, thereby enabling the creation of more comfortable women’s suits for consumers.